Catalytic Alkylation of 2-Aryl-2-oxazoline-4-carboxylic Acid Esters Using Cyclopeptoids; Newly Designed Phase-Transfer Catalysts - Schettini, Rosaria; D’Amato, Assunta; De Riccardis, Francesco; Della Sala, Giorgio; Izzo, Irene (Synthesis, 2017)
Nonionic, chiral macrocyclic peptoids are efficient phase-transfer catalysts in the C-4 enantioselective alkylation of 2-[4-(trifluoromethyl)phenyl]-2-oxazoline-4-carboxylic acid esters. Screening of the structural features of cyclic peptoids, namely the ring size, symmetry elements, number of proline residues, and substituents on the side chains, showed that the alternated N-(4-methoxybenzyl)glycine/l-proline cyclohexapeptoid is the optimal catalyst (good yields and up to 75% ee) for the stereocontrolled construction of α-alkylated serine tert-butyl esters.
Keywords: organocatalysis; asymmetric catalysis; phase-transfer catalysis; peptidomimetics; cyclopeptoids; α,α-dialkyl-α-amino acid